Predicting Financial Distress in the Indonesian Retail Industry (E-Jurnal Akuntansi, 2026)
The threat of financial distress necessitates that companies develop appropriate strategies to anticipate conditions that may lead to financial instability. One effective method for predicting financial distress is through the analysis of financial ratios. This study focuses on four key financial ratios: operating capacity, profitability, leverage, and cash flow, to examine their predictive power regarding financial distress. The research encompasses the entire population of retail sector companies in Indonesia, with data spanning from 2019 to 2022. The findings indicate that all four variables—operating capacity, profitability, leverage, and cash flow—are significant predictors of financial distress. Specifically, operating capacity, profitability, and cash flow exhibit a negative relationship with financial distress, suggesting that higher values in these variables are associated with lower financial distress risk. Conversely, leverage demonstrates a positive relationship, indicating that higher leverage increases the risk of financial distress. In conclusion, the study underscores the importance of these financial ratios in predicting financial distress within Indonesia's retail industry, highlighting the need for companies to monitor and manage these variables proactively to mitigate potential financial challenges.
Keywords: Financial Distress; Operating Capacity; Profitability; Leverage; Cash Flow